Aliens Are Just Like Us: Personal Names in The Legion of Super-Heroes. (2nd April 2016) - Sutton, Laurel
Abstract : Names created for alien comic-book characters in the 1960s provide an insight into cultural naming norms of the time; personal names had to be structurally familiar, so that readers could relate to them, yet different enough to seem other-worldly and/or futuristic. This analysis focuses on the personal names of The Legion of Super-Heroes, a team of super-powered teenagers from the thirty-first century. Their invented names conform sharply to English-speaking US American norms in terms of gender marking through syllable count and phonetic choice. The names of the future are very much like those of mid-twentieth-century American comic-book readers.